Coretax dan Krisis Kepercayaan Digital: Analisis Wacana Kritis terhadap Narasi Modernisasi Pajak di Media Online - Mohd Bahaudin Ihsan; I Nyoman Sudiana; I Nengah Suandi; I Putu Mas Dewantara (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
This article examines the discourse of Coretax as a digital tax modernization project in Indonesia by focusing on the tension between official narratives of integration, efficiency, and transparency and public/media narratives of disruption, error, data mismatch, and digital trust crisis. Using a qualitative approach with Critical Discourse Analysis, this study reviews selected online media texts, official public documents, press releases, and academic literature published between 2025 and 2026. The analysis employs Fairclough's three-dimensional model, supported by van Dijk's socio-cognitive perspective and van Leeuwen's legitimation framework. The findings show that Coretax is discursively constructed through three competing formations: modernization as technological necessity, disruption as administrative vulnerability, and recovery as institutional legitimation. The study argues that the crisis surrounding Coretax should not be interpreted merely as a technical problem, but as a discursive event that reveals the fragility of public trust in digital fiscal governance. Therefore, successful tax digitalization requires not only system stability but also transparent communication, accountable transition management, inclusive taxpayer assistance, and recognition of taxpayers as active civic subjects rather than passive users of technology.